IMPLEMENTASI FAILOVER CLUSTERING SERVER UNTUK MENGURANGI RESIKO DOWNTIME PADA WEB SERVER - Abdul Hakim; Meirina Suci Ridha; Sujiliani Heristian; Arina Selawati; Pradnya Paramita (Jurnal Akrab Juara, 2018)
The adoption of web servers in the world of office lately became quite important, as a result of the development of the desktop-based applications that have begun to shift toward Web-Based Applications. In reality, application of a web server in a company is not enough with just one web server, for the effectiveness of the work of the web server itself. Therefore, in this study the author tries to apply failover techniques on high availability clustering web server. Based on research methods that have been done writers begin with the analysis of needs, design, testing to implementation and data collection by way of observation, interview, and literature study, the application of failover techniques on high availability web server clustering is an attempt to minimize access failures that may occur anytime considering the state of the device that should standby at any time, where later after this technique is applied, then when the main server fails access to the application within the web server, the access will automatically be redirected to the second server. Keywords: Failover, High Availability, Web Server Clustering.